2005
DOI: 10.1080/15622970510029812
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation as a therapeutic tool in psychiatry

Abstract: Transcranial magnetic stimulation (TMS) is a patient-friendly stimulation technique of the brain with interesting perspectives. In clinical psychiatry, limited data are available on activity in psychosis and anxiety, but much research has been done in depression. Major concerns on published papers are the inconsistency of used parameter settings, the restraint numbers of patients in randomised trials, the lack of real sham controlled studies and the quasi inexistent reproducibility of results. The most stringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 152 publications
(197 reference statements)
0
15
0
Order By: Relevance
“…Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive technique with a treatment potential for a variety of neuropsychiatric illnesses (George et al, 2002;Simons and Dierick, 2005). Research has revealed the potential anti-craving effects of rTMS in substance dependence such as nicotine, cocaine and alcohol dependence (Barr et al, 2008, De Ridder et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive technique with a treatment potential for a variety of neuropsychiatric illnesses (George et al, 2002;Simons and Dierick, 2005). Research has revealed the potential anti-craving effects of rTMS in substance dependence such as nicotine, cocaine and alcohol dependence (Barr et al, 2008, De Ridder et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Currently, the physiological influence and treatment effects of repetitive TMS (rTMS) are under investigation. [3][4][5] As a focused cortical intervention, the majority of all treatment studies in depression target the dorsolateral prefrontal cortex (DLPFC) as the area of interest for rTMS. 6,7 However, it remains unclear which TMS parameters can produce the most benefits.…”
Section: Introductionmentioning
confidence: 99%
“…TMS produces brief magnetic pulses, which pass easily and painlessly through the skull and into the brain. TMS is commonly used to treat neurological and psychiatric disorders including mood disorders, dystonia, and Parkinson's disease [4]. TMS has been used for pain relief in chronic pain syndromes such as fibromyalgia, complex regional pain syndrome, and other neuropathic pain conditions [5].…”
mentioning
confidence: 99%